Kreativitas Guru Ipa Dalam Penyusunan Authentic Assessment Berdasarkan Kurikulum 2013 Di SMP NEGERI se-Kabupaten Kudus Semester Genap Tahun Ajaran 2014/2015 - Rachmawati, Shomayya, Dra. Hariyatmi, M.Si (2015)
Assessment is a process to determine whether the processes and results of a program of activities in accordance with the objectives or criteria that have been set. In the 2013 curriculum is authentic assessment becomes a serious emphasis which teachers in the assessment of learning outcomes really pay attention to authentic assessment. This research is aim to determine the creativity of science teachers in arranging of authentic assessment and appropriatability of arranging with the theory of the curriculum formulation of 2013 in of state junior high school in kudus. The type of this research is descriptive qualitative, data collection techniques are documentation of RPP and interviews with science teacher. Data obtained such as authentic assessment instruments which is arranging by a science teacher on its RPP on even semester academic year 2014/2015 and data interview about teachers information about authentic assessment, and analyzed using descriptive statistics. The result showed that the creativity of science teachers in preparing authentic assessment instruments in the assessment of observation (71.2%), self-assessment (90.1%), written assessment (50.7%), assessment assignment (62.5%), assessment of oral tests (54.1%), performance assessment (64.7%), project assessment (74.9%), portfolio assessment (0%), thus it can be concluded that the creativity of science teacher in arranging authentic assessment of state junior high s chool in kudus with the acquisition of a percentage of 64.1%, but still not good for appropriatability with the percentage of 34.8%